Prioritizing breast cancer surgeries: insights from the KRONOS SCORE - Navarro, Lucía; Perez-Bartivas, Luis; Ponferrada, David; Cejas, Javier; Camús, Juan Adrián; Rangel, Natalia; Porras, Maria; Morales Estevez, Cristina; Palacios Eito, Amalia; Rioja, Pilar; Alvarez, Marina; Aranda, Enrique; et al. (Frontiers in Oncology, 2025)
IntroductionIn many healthcare systems, the time to surgery (TTS) is used as a quality measure in breast cancer (BC) care. Although guidelines suggest that a waiting period of up to four weeks is acceptable, this is often exceeded, potentially impacting treatment outcomes. The COVID-19 pandemic highlighted the need to reassess surgical urgency. This study aims to explore the relationship between TTS and clinical outcomes in BC patients, focusing on how TTS influences final tumor stage and lymph node involvement.Materials and methodsA retrospective cohort study was conducted, including 924 women diagnosed with cT1-T3 BC without axillary lymph node involvement between 2014 and 2023. Preoperative staging was done using mammography and ultrasound, while postoperative staging relied on definitive anatomopathological reports. Statistical analyses included chi-square tests, Wilcoxon tests, and binary logistic regression. A prognostic score, the KRONOS SCORE, was developed based on significant variables from the final model, and internal validation was performed.ResultsOut of 924 patients, 781 had ductal carcinomas, 127 had lobular carcinomas, and 16 had other histologies. Breast-conserving surgery was performed on 664 patients, while 260 underwent mastectomy. TTS was less than 8 weeks for 513 patients and more than 8 weeks for 411 patients. No significant differences in tumor size changes were observed based on TTS. However, lymph node involvement increased from 23.8% in patients operated on within 8 weeks to 26.5% in those operated on after 8 weeks, with significant differences noted in poorly differentiated tumors (G3). The KRONOS SCORE, based on age, tumor grade, and size, was validated, showing a higher risk of lymph node involvement with higher scores.DiscussionAlthough TTS did not significantly affect most clinical and pathological parameters, a trend towards increased lymph node involvement with prolonged TTS was observed, particularly in patients with poorly differentiated tumors (G3). The KRONOS SCORE offers a tool for prioritizing surgical patients based on risk factors. However, further multicenter and prospective studies are needed to validate these findings and the KRONOS SCORE model’s effectiveness in different clinical settings.